Traditional Ecological Knowledge of the Tengger Tribe and its Influencing Factors in Bromo Tengger Semeru National Park - Susanto, Denni; Numata, Shinya (Jurnal Manajemen Hutan Tropika, 2023)
An understanding of the local traditional ecological knowledge (TEK) of a region is crucial to understand the interactions between indigenous societies and their ecosystems. To understand the TEK of Indonesian indigenous people and its influencing factors, we evaluated the Tengger people’s knowledge and conservation awareness regarding culturally important plants (Javanese edelweiss). We interviewed 641 people from seven Tengger villages located adjacent to Bromo Tengger Semeru National Park (BTS), Indonesia. We developed 31 models to examine factors affecting edelweiss knowledge and calculated the Akaike information criterion values to select the best model. Sex, education, and residency duration were significant predictors of edelweiss knowledge. Men, individuals with higher levels of education, and those who had lived in the area for a longer period of time had higher levels of edelweiss knowledge. Our findings confirm that communication within the community and external information sources, such as media and formal education, are involved in knowledge transmission related to edelweiss. Educational activities for local people can be used to disseminate TEK through formal education in schools and informal education programs conducted by the national park managers.